PERANAN BAHAN AMELIORAN RED MUD DAN PUPUK KANDANG SAPI TERHADAP KETERSEDIAAN HARA MAKRO DAN PERTUMBUHAN TANAMAN JAGUNG HIBRIDA DI TANAH GAMBUT - Jamli Jamli; Denah Suswati; Sulakhudin Sulakhudin (Fakultas Pertanian, Universitas Janabadra, 2024)
Peatlands have the potential to serve as productive agricultural land but possess low soil quality, necessitating innovative technologies to enhance soil quality and crop productivity. The improvement of peat soil quality can be achieved by utilizing ameliorants such as Red Mud and cattle manure. This study aims to investigate the role of Red Mud and cattle manure on the availability of macronutrients and the growth of hybrid corn plants in peat soil. The research was designed using a completely randomized design (CRD) with treatments of Red Mud and cattle manure. The first factor was Red Mud treatment at four dosage levels: without Red Mud (L0), 7 tons/ha (L1), 14 tons/ha (L2), and 21 tons/ha (L3). The second factor was cattle manure with four dosage levels: without cattle manure (P0), 50 tons/ha (P1), 100 tons/ha (P2), and 150 tons/ha (P3). The experiment was repeated three times, resulting in 48 experimental units. The results showed that the interaction between Red Mud and cattle manure significantly affected the parameters of exchangeable sodium availability and stem diameter. The single treatment of Red Mud had a significant effect on the parameters of pH, exchangeable potassium (K-dd), exchangeable sodium (Na-dd), cation exchange capacity (CEC), and plant height, with the best dosage being 21 tons/ha of Red Mud. The single treatment of cattle manure had a significant effect on the parameters of total nitrogen (N-total), available phosphorus (P-available), exchangeable potassium (K-dd), exchangeable sodium (Na-dd), and plant height, with the best dosage being 150 tons/ha of cattle manure. Keyword : amandement, peat soil, produktivity, quality